Archaeology of Sikkim Darjeeleing Himalayas - Chettri, Upasna (My University, 2025)
This study is undertaken in Sikkim-Darjeeling Himalayas. The archaeological evidences investigated are Megaliths and Pottery. The central objective of the thesis is to explore the material remains and anthropogenic markers of the past found in the study region. The study hypothesises that Sikkim had a megalithic culture and the existence of a pottery tradition in Sikkim and Darjeeling. In order to investigate the objectives of the study, the methodology opted is desk based assessment along with archaeological and ethnographic investigation for the recording and documentation of the archaeological evidences. For the analysis of the evidences, two different approaches were used.
Sharma, Sukanya